Avaliação da cultura de segurança do paciente na atenção primária à saúde - Galhardi, Nathalia Malaman (2017)
The patient safety as a fundamental dimension for health quality is focused on improvement provides care in the prevention of errors, in learning from them and in the involvement of all health professionals. It is more common heard about this subject in the hospital services, however, it is known that errors and consequently adverse events also occur in the Primary Health Care (PHC) compromising the patient safety. Despite the initiative of the organizations in promote the patient safety, the adherence on the services is still low, precisely because they does not have a culture focused on patient safety. It is understood that the organization culture and team attitudes can influence directly the quality of the results and for this reason it is necessary study this subject in this work place. The aim of this study was to evaluate the perception of professionals about the culture of patient safety in primary health care. This was a quantitative, cross-sectional, descriptive and correlational study of the type of survey. It was did in the period from December 2016 to March 2017 at the Family Health Centers (CSF) in a city in the interior of the State of São Paulo, where 564 professionals work. It was used the questionnaire "Patient Safety Culture for Primary Care" that evaluates twelve dimensions of the patient safety culture and the quality of care provided. The response rate was 52%. Seven of the twelve dimensions evaluated presented high reliability in the responses and were analyzed. For the dimensions "overall perception of patient safety and quality", "organizational learning", "information exchange with other settings", "teamwork", "patient care tracking", "patient safety and quality issues", the practitioners demonstrated a positive perception of the patient's safety culture. The "leadership support" dimension has proven to be a weak area for the patient's safety culture. In the overall assessment of patient safety and quality of care, the service was rated by the participants as "Good". In the comparison of the variables of service time and professional category with the average of the percentages of positive responses there was a significant difference. For service time the lower the time the greater the positive perception for the dimensions "organizational learning" and "leadership support" and as for professional category, the physician showed more positive perception for the dimensions "overall perception of patient safety" and "teamwork". It was concluded that most of the dimensions presented had positive scores in the assessment of the patient safety culture and that the dimension that most needs improvement and actions focused on patient safety are mainly to the leadership. It is necessary to support a just culture, where the professional does not feel threatened from the occurrence of the error. Leadership involvement in patient safety encourages a safe and secure environment.